Study of the effects of roasting and sodium thiosulfate on the extraction of silver from Volcanic Massive Sulfide ore - AL motasim Tambal; Abdalla Suliman; Abdelmajid Ibrahim; Essam Mohamed; Mohammed Kabashi (Results in Chemistry, 2023)
The main objectives of this article were to firstly decrease the amount of sulfide in the (Volcanic Massive Sulfide –VMS) in the eastern Sudan (Ariab) area through a roasting pretreatment, secondly determine the best and optimum (thiosulfate concentration – ammonia concentration – copper sulfate concentration - leaching time – pH) for extracting silver sulfide metal (Ag2S) also known as argentite from the same ore, thirdly using sodium cyanide concentration equal to the optimum thiosulfate concentration obtained from the experiments to determine which solvent is better at the same concentrations thiosulfate or cyanide.The leaching process took place at different concentrations, times, following a roasting pre-treatment at (300–400-500–600-700 °C), The Analytics of (ICP) and (XRF) showed that silver concentration is (10.91 PPM), iron is (15.76 PPM) and copper is (119.16 PPM), and the (SEM) analysis showed that Sulfur is present in the proportion of (26 %) in the ore, and from the study of fractions it became clear that the highest presence of silver was at the size (-106 + 75) micron.It was found that the best roasting temperature was (700 °C), and the best extraction using sodium thiosulfate was (61.06 %) at thiosulfate concentration (0.2 M) and ammonia concentration (0.2 M), time (6) hours, copper sulfate concentration (0.05 M), pH (10) and pulp density (25 %) at room temperature. As for sodium cyanide at the same concentration (0.2 M), it was found that the extraction was (49.47 %) at time (6) hours, pH (10), and pulp density (25 %). At room temperature, it was clear that cyanide was less efficient at (0.2 M) concentration than thiosulfate in dissolving silver.